Analisis Faktor Yang Berhubungan Dengan Kelelahan Driver Ojek Online di Kota Makassar - Ar-Syam, Aldy Rizaldi Febrian; Erlani; Ronny (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2023)
Fatigue is a symptom experienced by a person caused by psychological and physical factors and fatigue is also a condition where a person feels very tired, tired or sleepy due to lack of sleep, and prolonged physical work. Work fatigue that occurs in online motorcycle taxi drivers which is characterized by the appearance of symptoms such as drowsiness, dizzy vision, feeling very tired, body and legs feel sore. (Agustina & Lupita, 2019).The purpose of this study was to determine the factors associated with the fatigue of online grab bike motorcycle taxi drivers in Makassar City. This type of research is an analytical observational cross sectional approach with a population of 1,142 online motorcycle taxi drivers with a sample of 92 respondents. The sampling technique was obtained through direct interviews with respondents with an instrument in the form of a questionnaire sheet. Data analysis was univariate and bivariate using chi square test.The results of this study indicate that there is no relationship between fatigue and age with P value = 0.099 (ρ>α 0.05), Work Period P value = 0.457 (ρ>α 0.05), Length of Work P value = 0.033 (ρ< 0.05), and Sleep Quantity P value = 0.021 (ρ < 0.05), has a relationship with fatigue.The conclusion is there is no relationship between age and working period with fatigue, there is a relationship between length of work and sleep quantity with Fatigue of Online Grab Bike Ojek Drivers Suggestions for online motorcycle taxi drivers Add insight about good safety riding, so that good driver knowledge will reduce the risk of work fatigue, and drivers must also rest and avoid excessive working time.